2005
DOI: 10.1124/jpet.104.074849
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Involvement of Nitric Oxide in 3,4-Methylenedioxymethamphetamine-Induced Serotonin Depletion in the Rat Brain

Abstract: Production of reactive oxygen and/or nitrogen species has been thought to contribute to the long-term depletion of brain dopamine and serotonin (5-HT) produced by amphetamine derivatives, i.e., methamphetamine and 3,4-methylenedioxymethamphetamine (MDMA). In the present study, the effects of nitric-oxide synthase (NOS) inhibitors were examined on the long-term depletion of striatal dopamine and/or 5-HT produced by the local perfusion of malonate and MDMA or the systemic administration of MDMA. The effect of MD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
34
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 36 publications
7
34
0
Order By: Relevance
“…The authors postulated that MDMA depletes 5-HT by increasing tyrosine brain concentration, which can be converted to DA within 5-HT terminals [411]. Another study reported that MDMA (10 mg/kg×4, i.p., every 2 h) also promoted an elevation of extracellular tyrosine concentrations in the striatum of male Sprague-Dawley rats [412]. Posterior MAO metabolism of this monoamine would explain free radical formation inside the nerve terminal that would lead to degeneration.…”
Section: Da Substantial Release Promoted By Mdmamentioning
confidence: 97%
“…The authors postulated that MDMA depletes 5-HT by increasing tyrosine brain concentration, which can be converted to DA within 5-HT terminals [411]. Another study reported that MDMA (10 mg/kg×4, i.p., every 2 h) also promoted an elevation of extracellular tyrosine concentrations in the striatum of male Sprague-Dawley rats [412]. Posterior MAO metabolism of this monoamine would explain free radical formation inside the nerve terminal that would lead to degeneration.…”
Section: Da Substantial Release Promoted By Mdmamentioning
confidence: 97%
“…Thus, free radical scavengers and antioxidants attenuate MDMA-induced 5-HT deficits (for review see Capela et al, 2009;Puerta et al, 2009a), providing indirect evidence for the involvement of free radicals in the mechanism of MDMA neurotoxicity. In addition, MDMA has been reported to produce cellular changes, e.g., lipid peroxidation or protein nitration, consistent with the formation of free radicals (Sprague and Nichols, 1995;Colado et al, 1997;Darvesh et al, 2005). Finally, Colado et al (1997) and Shankaran et al (1999) demonstrated that MDMA increases the formation of 2,3-dihydroxybenzoic acid from salicylate in hippocampal and striatal dialysates, a conversion that occurs in the presence of a high concentration of free radicals, an effect reversed by ascorbic acid (Shankaran et al, 2001).…”
mentioning
confidence: 88%
“…On the other hand, it has been shown that MDMA increases nitrotyrosine formation, which is a stable marker of peroxynitrite formation (Darvesh et al, 2005), a highly reactive anion formed in the reaction of nitric oxide (NO) with superoxide radicals (Ischiropoulos and al-Mehdi, 1995). Accordingly, we next studied the effects of sildenafil pretreatment on nitrotyrosine formation caused by MDMA (3 3 5 mg/kg i.p.).…”
Section: Effect Of Sildenafil On Mnsod Expression Superoxide Productmentioning
confidence: 99%
“…The importance of decreased ATP levels in amphetamine toxicity is demonstrated by an experiment where neural glucose uptake was prevented by administration of 2-deoxyglucose, a manipulation that enhanced both the decrease in ATP levels observed directly after METH treatment as well as the loss of striatal DA 1 week later (Chan et al, 1994). Similarly, inhibition of metabolism by directly interfering with the ETC also increases toxicity because the potent complex II inhibitor malonate exacerbated both METH and MDMA toxicity (Burrows et al, 2000;Darvesh et al, 2005), whereas application of the energy substrates decylubiquinone or nicotinamide 6 hours after METH treatment reduced toxicity (Stephans et al, 1998).…”
Section: Action Of Substituted Amphetamines and Cathinonesmentioning
confidence: 99%